Beverage Consumption by 0-3 Year-Old Children and its Relation with Dental Fluorosis Severity - Loliza Chalub Luiz FIGUEIREDO; Carolina de Castro MARTINS; Nircinara Reis PINHEIRO; Saul Martins de PAIVA (Association of Support to Oral Health Research (APESB), 2006)
Objective: To evaluate the beverage ingested by children between 0 and 3 years old and their relation to the different degrees of dental fluorosis. Method: Four hundred and twenty nine children, between 6 and 12 years old, from Levindo Lopes Municipal School in Belo Horizonte-MG (0.74 ppm F) have been submited to clinical examination. One hundred and thirty four children were diagnosed as having dental fluorosis in grades varying from questionable to moderate. The parents of these children answered a questionnaire about milk, teas and juices ingestion by them when they were between 0 and 3 years old. For statistical analysis it was used the SPSS 9.0.0 program and Fisher's exact test (p≤0.05). Results: It was noted that the ingestion of maternal milk, bovine milk, juices and teas by children between 0 and 3 years old was common, although none of these factors has had significant association with the degrees of dental fluorosis. Conclusion: The highest frequency of juices ingestion was significantly associated with highest degrees of dental fluorosis (p=0.046). Parents should be informed about the role of industrialized beverages in the ingestion of fluorides.